A cognitive assessment tool designed for data collection in the field in low- and middle-income countries. (March 2019) - Ford, Cassie B; Kim, Ha Yeon; Brown, Lindsay; Aber, J. Lawrence; Sheridan, Margaret A.
The Rapid Assessment of Cognitive and Emotional Regulation (RACER) is a tablet-based assessment tool for children that measures executive function (EF) skills. Instructions that are brief and visually presented; game-like tasks are designed to easily engage children regardless of literacy level and variable test administration settings. RACER measures inhibitory control and working memory. This study presents the theoretical rationale and empirical evidence for tablet-based assessments of EF, the process of administering the RACER assessments. The current sample consists of students in Lebanon (N=1900) and Niger (N=850). The results indicate that individual differences in EF can be assessed by the RACER tablet tasks. Specifically, we demonstrate that EF scores are associated in expected ways with age and that tasks function similarly to what has been observed in high-income countries. The feasibility and utility for researchers, practitioners, and clinicians, of this cognitive assessment tool is discussed.